Service marketing strategies for small and medium enterprises emerging research and opportunities - Muhammad Sabbir Rahman; Zaman, Mahmud Habib 1981-; Hossain, Md Afnan 1987- (IGI Global, 2019)
"This book addresses the growing importance of services and in recognition of unique challenges faced by small and medium enterprises service marketing managers to gain insights and a level playing field thereby attaining sustainability. It also focuses on the knowledge required to implement service strategies to gain competitive advantages"...